Temperature-related variations in physical performance during elite soccer matches - Pavlinovic, V.; Morgans, R.; Modric, T. (Sports, 2024)
The aim of this study was to examine the differences in match running performance (MRP) according to the ambient temperature during UEFA Champions League (UCL) matches. Data were collected using an optical tracking system from all teams (n = 32) in all UCL matches (n = 125) during the 2022/23 season, and classified according to the ambient temperature at which matches were played: <5 °C, 6-10 °C, 11-20 °C, and >21 °C. The results revealed the following: (i) less total distance was covered in matches played at =21 °C compared to the matches played at 6-10 °C (d = 0.58), (ii) less high-speed running and high-intensity running were covered in matches played at =21 °C compared to the matches played at 11-20 °C (d = 0.54 and 0.43, respectively), 6-10 °C (d = 0.89 and 0.8, respectively), and =5 °C (d = 0.62 and 0.57, respectively), and (iii) less sprinting was covered in matches played at =21 °C compared to the matches played at 6-10 °C (d = 0.22). These findings indicated the significant differences in MRP when UCL matches were played at different ambient temperatures, with notable reductions in overall and high-intensity efforts in warmer conditions.